Transimmanence and the Im/possible Relationship between Eschatology and Transcendence - Anné Hendrik Verhoef (Religions, 2016)
Although we live in a post-metaphysical age, there is a renewed interest in transcendence, especially at the intersection of philosophy, religion, and theology. There are several reasons for this: among others, the important link that the future (eschatology) has with the unknown or that which lies beyond (transcendence). In this article, this relation between eschatology and transcendence is explored by analysing different concepts of transcendence and their possible relations to the future. Jacques Derrida and Catharine Malabou’s concepts of the future are used to shed light on the link between eschatology and transcendence as “impossible”. Secondly, Jean-Luc Nancy’s concept of transimmanence is introduced, in an attempt to find such a possible link. A reconceptualisation of transcendence as transimmanence and a reconceptualisation of the future of eschatology as something “outside within”, facilitate a link between these terms, but the original or general meanings of these terms then become impossible. This outcome urges a rethinking of the meaning and role of transcendence, eschatology, and the future in our post-metaphysical age.